Warning [videorecording (DVD)] - Alexander, Agata; Eve, Alice, 1982-; Wallis, Annabelle, 1984-; Jane, Thomas (Lionsgate, 2021)
Set in the not too distant future, this intense sci-fi thriller explores the repercussions that mankind faces when their omniscient technology becomes a substitute for human contact. But life begins to unravel when a global storm causes electronics to go haywire, leading to terrifying, deadly consequences.